Vaccine wastage at the level of service delivery: a cross-sectional study. (July 2017) - Duttagupta, C.; Bhattacharyya, D.; Narayanan, P.; Pattanshetty, S.M.
Highlights: Wastage rates of vaccines were observed to be higher than the recommended limits. Ten-dose vials were observed to have high wastage compared with other vial sizes. Lyophilized vaccines were observed to have more wastage than liquid vaccines. Wastage is unavoidable to ensure high coverage but avoidable causes need monitoring. Baseline results can help identify scope of improvement in management practices.